2005
DOI: 10.1016/j.femsre.2005.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Overview on sugar metabolism and its control in – The input from in vivo NMR

Abstract: The wide application of lactic acid bacteria in the production of fermented foods depends to a great extent on the unique features of sugar metabolism in these organisms. The relative metabolic simplicity and the availability of genetic tools made Lactococcus lactis the organism of choice to gain insight into metabolic and regulatory networks. In vivo nuclear magnetic resonance has proven a very useful technique to monitor non-invasively the dynamics of intracellular metabolite and co-factor pools following a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 192 publications
(229 reference statements)
1
69
0
Order By: Relevance
“…A weak galactose phenotype was found for the SP0090-1-2 CUT1 ABC transporter mutant which showed reduction in sugar utilization in the phenotype microarray where a 15% reduction in redox potential generation was measured. Galactose, when imported by ABC transporters or permeases, is phosphorylated intracellularly at the C1 position by a specific kinase (GalK) and metabolised not by the tagatose-6-phosphate pathway, but by the Leloir pathway [97] . The necessary genes are not in a conserved operon structure in the diverse lactic acid bacteria [98].…”
Section: Resultsmentioning
confidence: 99%
“…A weak galactose phenotype was found for the SP0090-1-2 CUT1 ABC transporter mutant which showed reduction in sugar utilization in the phenotype microarray where a 15% reduction in redox potential generation was measured. Galactose, when imported by ABC transporters or permeases, is phosphorylated intracellularly at the C1 position by a specific kinase (GalK) and metabolised not by the tagatose-6-phosphate pathway, but by the Leloir pathway [97] . The necessary genes are not in a conserved operon structure in the diverse lactic acid bacteria [98].…”
Section: Resultsmentioning
confidence: 99%
“…Their natural habitat is plant and raw food materials (milk, meat, vegetables, cereals). They are characterized by a simple carbohydrate (carbon/energy source) and protein (nitrogen source) metabolism, a limited number of related biosynthetic capacities and small genomes (Hols et al, 2005;Klaenhammer, Barrangou, Buck, Azcarate-Peril, & Altermann, 2005;Kok, Buist, Zorner, van Hijum, & Kuipers, 2005;Neves, Pool, Kok, Kuipers, & Santos, 2005). The acidification and enzymatic processes (e.g., pyruvate metabolism, amino acid bioconversions, bacteriocin production and exopolysaccharide biosynthesis), accompanying the growth of LAB, impart the preservative qualities, texture and key flavour to a variety of fermented foods and beverages (Leroy & De Vuyst, 2004;Wood, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…A combination of [U- 13 C] glucose and [1- 13 C] has generally been used to decipher the relative fluxes connecting the lower part of glycolysis and the TCA cycle. In this study, the flux ratios indicated that 60% of PEP was contributed by glycolysis, suggesting a substrate level phosphorylation in L. lactis , by converting sugars via the glycolytic pathway (Neves et al, 2005). Additionally, it has been reported that L. lactis growth on minimal glucose (55 mM) led to the formation of extremely homolactic fermentation by increasing the activities of phosphofructokinase (PFK), pyruvate kinase (PYK) and lactate LDH and therefore led to accumulation of lactate (Papagianni, Avramidis & Filiousis, 2007).…”
Section: Resultsmentioning
confidence: 67%